Effect of intraoperative low-dose esketamine infusion on postoperative sleep disturbance after laparoscopic cholecystectomy: a randomized clinical trial - Yanan Wu; Yaning Yang; Xiaomei Wang; Li Sun; Yunpeng Hei; Yuhua Zou; Zhenhai Ye; Zhi Yu (BMC Anesthesiology)
Abstract Background Postoperative sleep disturbance (PSD) is a common surgical complication. In this study, we investigated the effect of intraoperative esketamine infusion on the incidence of PSD in patients who underwent laparoscopic cholecystectomy. Methods A single-center, double-blinded, placebo-controlled randomized clinical trial was perfomed from May to August 2024 at the People’s Hospital of Ningxia Hui Autonomous Region. Study participants included patients aged ≥ 18 years, ASA classification of I to III, BMI of 18 to 30 kg/m2 and underwent laparoscopic cholecystectomy. Patients were randomly assigned to esketamine group or placebo group using a random number table method. Patients in the esketamine group received continuous intraoperative infusion of esketamine, 0.5 mg/kg/h while those in the placebo group were given an equal volume of normal saline. The primary outcome was PSD incidence within 1–3 postoperative days (PODs). PSD was defined as numerical rating scale score of 6 or higher or Athens Insomnia Scale score of 6 or higher. Secondary outcomes were postoperative pain (using visual analog scale), intraoperative remifentanil consumption, postoperative adverse reactions, and PSD-related risk factors. Results Eighty-six patients were randomly assigned to esketamine group (n = 43; mean [SD] age, 47.9 [9.4] years) and placebo groups (n = 43; mean [SD] age, 49.7 [15.1] years). The incidence of PSD in the esketamine group was significantly lower than in the control group on POD 1 (58.1% vs. 81.4%;​ odds ratio [OR], 0.32 [95%Cl, 0.12–0.84]; P = 0.019) and POD 2 (11.6% vs. 44.2%; OR, 0.17 [95%Cl, 0.06–0.50]; P = 0.001) and POD3 (2.3% vs. 18.6%; OR, 0.10 [95%Cl, 0.01–0.87]; P = 0.035). Postoperative pain score and intraoperative remifentanil consumption in the esketamine group were lower than those in the placebo group (all P < 0.05). There was no difference in postoperative adverse reactions between the two groups. Multivariate logistic regression analysis showed that operation duration (P = 0.049), ASA grade (P = 0.044), and drain insertion (P = 0.021) were independent risk factors for PSD. Conclusion Intraoperative infusion of low-dose esketamine can prevent the incidence of PSD in patients undergoing laparoscopic cholecystectomy. Further studies are required to confirm these results. Trial registration Chinese Clinical Trial Registry (ChiCTR2400083826).